Clinical features of hepatolithiasis: analyses of multicenter-based surveys in Japan. Issue 1 (December 2015) - Tazuma, Susumu; Nakanuma, Yasuni
Abstract Background Hepatolithiasis is a calculus disease of the liver with no known cause that is relatively uncommon, and is characterized by a refractory nature and high frequency of recurrence. Hepatolithiasis is one of the diseases listed by the Ministry of Health, Labour and Welfare of Japan under Research on Intractable Diseases, and it requires further research on the pathogenesis as well as the therapeutic strategy. It is also included in the clinical guidelines for cholelithiasis of the Japanese Society of Gastroenterology, which suggest guiding principles for the treatment of hepatolithiasis. Methods we performed questionnaire surveys of hepatolithiasis twice in 2010 and in 2012. Verification of the evidence-based clinical practice guidelines a questionnaire survey of 22 facilities in 2010 and 25 facilities in 2012 across Japan that provided cooperation, which enabled us to assess 210 new cases over a two-year period. Conclusions Comparison with two surveys that have been carried out previously revealed the main factor associated with hepatolithiasis was a history of biliary tract surgery, which was noted in the majority of cases. In addition, there was an increase of patients in whom balloon endoscopy was performed using transduodenal approach. This method is not included in the treatment options of the current clinical guidelines for cholelithiasis, so there may be a need to take it into consideration when the guidelines are revised.